A new species of Paravelia Breddin, 1898 (Hemiptera: Heteroptera: Veliidae) from Colombia, with a key to Colombian Paravelia species - Padilla-Gil, Dora Nancy; Moreira, Felipe Ferraz Figueiredo (Zootaxa, 2011)
Paravelia daza sp. n. is described, including details of internal morphology, and compared with P. inveruglas (Kirkaldy) from Ecuador, a similar species within the genus. An identification key including P. daza sp. n., P. columbiensis (Hungerford), P. flavomarginata (Hungerford) and P. recens (Drake & Harris), the four species of Paravelia so far recorded from Colombia, is also presented.